Unique journey of a fallen gall stone leading to gastrointestinal, biliary and intraperitoneal haemorrhage: The first case in the literature - Mehmet Celal Kızılkaya; Fazilet Erözgen; Ahmet Kocakuşak; Cihad Tatar; Rafet Kaplan (Turkish Journal of Gastroenterology, 2019)
-